Peningkatan Daya Saing Usaha Berdasarkan Implementasi Strategi Kemitraan Usaha - Makatita, Muhajir; Niapele, Sarifa; Balik, Dessy (Program Studi Administrasi Niaga STIA Said Perintah, 2022)
This study aims to examine and analyze the effect of business partnership strategies on business competitiveness. This type of research is explanatory research using a quantitative approach. The population in this study is the total of 80 groups of seaweed cultivation business actors in Southeast Maluku Regency who have formed partnerships. Sampling using purposive sampling technique with a final sample of 80 respondents. Methods of data analysis using quantitative analysis. The analytical model used is simple regression. The results of this study prove that the business partnership strategy has a positive impact on increasing business competitiveness. The results of this study also prove that the business partnership strategy has a contribution (determination) of 60% towards increasing the competitiveness of the seaweed cultivation business in Southeast Maluku Regency.